1999
DOI: 10.1002/1529-0131(199911)42:11<2356::aid-anr14>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Serum cartilage oligomeric matrix protein reflects osteoarthritis presence and severity: The Johnston county osteoarthritis project

Abstract: Objective. To characterize serum cartilage oligomeric matrix protein (COMP) levels by age and gender for a radiographically defined population free of hip and knee osteoarthritis (OA), and to examine the potential utility of COMP as a diagnostic biomarker for knee OA.Methods. Serum samples and knee and hip radiographs were obtained at a baseline evaluation as part of the Johnston County Osteoarthritis Project, a population-based study of OA in rural North Carolina. A total of 291 Caucasian participants were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
156
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 235 publications
(169 citation statements)
references
References 25 publications
10
156
2
1
Order By: Relevance
“…COMP, a member of the thrombospondin family of proteins, has been shown to be increased in the serum of patients with OA and those with RA (38,39). In this study, MMP-12 was particularly active with respect to generating COMP-derived peptide fragments.…”
Section: Identification Of Peptides Formed By Metalloprotease Cleavagmentioning
confidence: 54%
“…COMP, a member of the thrombospondin family of proteins, has been shown to be increased in the serum of patients with OA and those with RA (38,39). In this study, MMP-12 was particularly active with respect to generating COMP-derived peptide fragments.…”
Section: Identification Of Peptides Formed By Metalloprotease Cleavagmentioning
confidence: 54%
“…A few of these studies have also investigated the radiographic severity of OA and serum or urinary biochemical markers (18)(19)(20)(21)(22)(23). In the present study, we analyzed the largest panel of biochemical markers ever investigated in a wellcharacterized cohort of patients with knee OA and we observed that 14 of them were significantly associated with at least 1 imaging feature.…”
Section: Discussionmentioning
confidence: 73%
“…To our knowledge, this has not been done in previous studies of MMP-3 as a biomarker of OA. However, in a study of subjects with OA in which both hips and both knees were evaluated, Clark et al (31) reported that the serum level of cartilage oligomeric matrix protein (COMP) increased significantly with the number of affected joints. Similarly, Sowers et al (32) found that serum concentrations of the acute-phase reactant CRP were significantly higher among women with bilateral knee OA than among those with unilateral disease.…”
Section: Lohmander Et Almentioning
confidence: 99%